Knowledge, attitude and practice of surgical site infection prevention among nurses in surgical ward - Lee, Siew Pien (2019)
Background: Surgical site infection (SSI) is an infection that occur after operation that involves the skin, subcutaneous tissue of the incision, the deep soft tissue of the incision, any part of anatomy other than the incision that was opened during an operation occurred within 30 days. Nurses play an important in initiatives that aim to minimize the risk of SSI, and thus to enhance patient safety. Aim: The purpose this study was to identify the level of knowledge, attitude and practice regarding SSI prevention among nurses, and also to determine the association between the socio-demographic data with the knowledge, attitude and practice regarding SSI prevention among nurses in surgical ward by using questionnaires as instrument. Method: We used the cross-sectional descriptive study design in this research. The sampling method was convenience sampling. The population for this study was staff nurses who work in surgical wards in Tengku Ampuan Afzan Hospital (HTAA). A total of 91 nurse took part in this study. This research used a set of set-administrated questionnaire that could be divided into four part. Part A consist of demographic data questions. Part B questionnaire for knowledge of SSI prevention (score range 0 - 9). Part C was questions for attitude towards SSI prevention (score range 10 - 40). Last part, part D was questions for practice of nurses regarding SSI prevention (score range 11 - 44). Results: The findings showed that majority of the staff nurses in HTAA, Kuantan, Pahang had low level of knowledge with the percentage of 65.9% compared to high level of knowledge with the percentage of 34.1%. The positive attitude (95.6%) towards SSI prevention while, only 4.4% of them had negative attitude towards SSI prevention. The majority of nurses (98.9%) have good practice in preventing SSI. There was only age and education have a significant association with the level of knowledge with p value of 0.022 and 0.037 respectively. Whereas, the years of service, years of experiences and training have no association with the level of knowledge with p value of 0.674, 0.558 and 0.054 respectively. There was significantly association between the years of experiences and the attitude of nurses towards SSI prevention (p-value=0.047). However, the age, level of education, years of service and training were not significantly associated with the attitude of the nurses with p value > 0.05. There was no association between socio-demographic (age, level of education, years of service, years of experience, and training) and the level of practice of the nurses with p value > 0.05. Conclusion: The study has given evidence of inadequate nursing knowledge regarding SSI prevention among nurse in surgical ward. Thus, there is a need for hospital organization to conduct a continuing in-service educational program in relation to SSI prevention. Efficient knowledge and good practices by the nurses can facilitate patient care and may contribute to decrease the rate of infection in the hospitals.